AEROsol generic classification using a novel Satellite remote sensing Approach (AEROSA) - Bilal, Muhammad; Ali, Md. Arfan; Nichol, Janet E.; Bleiweiss, Max P.; de Leeuw, Gerrit; Mhawish, Alaa; Shi, Yuan; Mazhar, Usman; Mehmood, Tariq; Kim, Jhoon; Qiu, Zhongfeng; Qin, Wenmin; et al. (Frontiers in Environmental Science, 2022)
Numerous studies (hereafter GA: general approach studies) have been made to classify aerosols into desert dust (DD), biomass-burning (BB), clean continental (CC), and clean maritime (CM) types using only aerosol optical depth (AOD) and Ångström exponent (AE). However, as demonstrated in this paper, AOD and AE do not provide sufficient information to unambiguously classify aerosols into these four types. Evaluation of the performance of GA classification applied to AErosol Robotic NETwork (AERONET) data, at sites for situations with known aerosol types, provides many examples where the GA method does not provide correct results. For example, a thin layer of haze was classified as BB and DD outside the crop burning and dusty seasons respectively, a thick layer of haze was classified as BB, and aerosols from known crop residue burning events were classified as DD, CC, and CM by the GA method. The results also show that the classification varies with the season, for example, the same range of AOD and AE were observed during a dust event in the spring (20th March 2012) and a smog event in the autumn (2nd November 2017). The results suggest that only AOD and AE cannot accurately classify the exact nature (i.e., DD, BB, CC, and CM) of aerosol types without incorporating more optical and physical properties. An alternative approach, AEROsol classification using Satellite remote sensing Approach (AEROSA), is proposed where the AOD and AE from AERONET Version 3 Level 2.0 data and the Terra-MODIS (MODerate resolution Imaging Spectroradiometer) Collection 6.1 Level 2 combined Dark Target and Deep Blue (DTB) product are used to assign generic aerosol types for each situation. Although AEROSA is also based on AOD and AE, it does not claim the nature of aerosol types. The purpose is to introduce AEROSA for those researchers who are interested in classifying aerosol types based on AOD and AE, then generic aerosol types can be considered, without claiming the exact nature of aerosol types. AEROSA not only provides 9 generic aerosol types for all observations but can also accommodate variations in location and season.